# Find length of the arc of $y^2=x$

I am embarrassingly stuck on this example. My textbook provides the answer (picture below) and the steps, but I am unable to follow the math. I have been stuck for more then an hour.

Find the length of the arc of the parabola $$y^2=x$$ from (0,0) to (1,1).

Since $$x=y^2$$, we have $$\frac{dx}{dy} = 2y$$.

\begin{align} L &= \int_{0}^{1} \sqrt{1+(\frac{dx}{dy})^2}dy \\ &= \int_{0}^{1} \sqrt{1+(2y)^2}dy \end{align}

Here is where I am getting stuck. I am supposed to make a trigonometric where $$y = \frac{1}{2}\tan\theta$$, but based off the trig substitution equation I have, $$\sqrt{a^2+y^2} \rightarrow y = \tan\theta$$ I am getting confused how I am supposed to get $$y = \frac{1}{2}\tan\theta$$. I keep thinking it should be $$y = \frac{1}{4}\tan\theta$$.

Here is where I get my $$y$$ value from: $$\sqrt{a^2 + y^2} = \sqrt{1+ 2^2 y^2} \\ = \sqrt{\frac{1}{4} + y^2}$$ Which gives me $$y = \frac{1}{4} tan\theta$$

Here is a picture of the example in the textbook. I am not able to follow the math :(

If you have a sum under the square root sign ($$\sqrt{a^2+x^2}=\sqrt{\frac{1}{a^2}\left(1+a^2x^2\right)}=\frac{1}{a}\sqrt{1+a^2x^2},\ a>0$$), your trigonometric substitution would be $$x=\frac{1}{a}\tan{\theta}$$:
$$\int\sqrt{1+4y^2}\,dy=\int\sqrt{1+2^2y^2}\,dy\rightarrow y= \frac{1}{2}\tan{\theta}, dy=\frac{dy}{d\theta}d\theta= \frac{1}{2}\sec^2\theta\,d\theta\\ \int\sqrt{1+4\left(\frac{1}{2}\tan{\theta}\right)^2}\frac{1}{2}\sec^2\theta\,d\theta= \frac{1}{2}\int\sqrt{1+4\cdot\frac{1}{4}\tan^2{\theta}}\sec^2\theta\,d\theta=\\ \frac{1}{2}\int\sqrt{1+\tan^2{\theta}}\sec^2\theta\,d\theta= \frac{1}{2}\int\sqrt{\sec^2\theta}\sec^2\theta\,d\theta=\\ \frac{1}{2}\int|\sec{\theta}|\sec^2\theta\,d\theta= \frac{1}{2}\int\sec^3\theta\,d\theta.$$
Here, $$\sec\theta>0$$, so we can drop the absolute value sign. That's because we're considering only an interval on which the secant function is positive (the interval of choice is typically $$0<\theta<\frac{\pi}{2}$$).
"Here is where I get my $$y$$ value from: $$\sqrt{a^2 + y^2} = \sqrt{1+ > 2^2 y^2} \\ > = \sqrt{\frac{1}{4} + y^2}$$ Which gives me $$y = \frac{1}{4} tan\theta$$"
From here you want not $$y = \frac{1}{4} \tan\theta$$ but $$y^2 = \frac{1}{4} \tan^2\theta$$. Taking square roots gives $$y = \frac{1}{2} \tan\theta$$.